Temperature and trophic structure are driving microbial productivity along a biogeographical gradient. Issue 10 (9th December 2015) - Gray, Sarah M.; Poisot, Timothée; Harvey, Eric; Mouquet, Nicolas; Miller, Thomas E.; Gravel, Dominique
Abstract : Temperature is known to influence ecosystem processes through its direct effect on biological rates such as respiration and nutrient cycling. These changes can then indirectly affect ecologically processes by altering trophic dynamics, the persistence of a species in a given environment, and, consequently, its distribution. However, it is not known if this direct effect of temperature on biological rates is singularly the most important factor for the functioning of ecosystems, or if trophic structure and the adaptation of a species to the local environment also play an essential role. Understanding the relative importance of these factors is crucial for predicting the impact that climate change will have on species and ecosystems. To achieve a more complete understanding of the impact of changing temperatures, it is necessary to integrate perspectives from biogeography, such as the influences of species distribution and local adaptation, with ecosystem and community ecology. By using the microbial community inhabiting the water‐filled leaves of Sarracenia purpurea, we tested the importance of temperature, trophic structure, and local adaptation on ecosystem functioning. We accomplished this by collecting communities along a natural temperature gradient and maintaining these communities in a common garden, factorial experiment. To test for the importance of local adaptation and temperature, the origin of each community was crossed with the temperature from each site. Additionally, to test the importance of top‐down trophic regulation for ecosystem functioning, the presence of the mosquito larvae top predator was manipulated. We found that temperature has a greater effect on ecosystem functioning than origin, and that top‐down trophic regulation increased with temperature. Our results emphasize the synergistic effects of temperature and biotic interactions when predicting the consequences of global warming on ecosystem functioning.